Beyond the Baseline: A Multifactorial Review of Tennis Injuries - Tłoczek, Wiktoria; Twardowska, Daria; Śliwa, Wiktoria; Szlachta, Wiktoria; Kret, Dominik; Zdziebko, Aleksandra; Dziuk, Kamil (Quality in Sport, 2026)
Background: Tennis is widely practiced globally across all ages and skill levels. The sport involves high-speed strokes, rapid directional changes and complex kinetic-chain movements, placing substantial demands on the musculoskeletal system. Repetitive and asymmetrical actions, especially during the serve, increase the risk of acute and overuse injuries. Aim: To provide an overview of the epidemiology, mechanisms, risk factors, as well as prevention strategies for tennis-related injuries across recreational, junior, and elite players, highlighting research gaps. Material and Methods: A systematic review was conducted using PubMed, focusing on English-language peer-reviewed studies. Epidemiological and biomechanical assessments, intervention trials and professional injury surveillance data were analysed to summarize injury patterns, mechanisms, risk factors with preventive strategies. Results: Injuries are most frequent in lower extremities, followed by upper extremities and trunk, with muscle–tendon injuries predominating. Shoulder injuries result from repetitive overhead actions, while ankle sprains and patellar tendinopathy arise from acute trauma or chronic overload. Risk factors include prior injury, kinetic-chain deficits, workload spikes, court surface and sex differences. Prevention requires workload management, kinetic-chain conditioning, serve-specific biomechanics, core stability, functional screening, combined with psychological support. Conclusions: Tennis injuries are multifactorial, with the serve central to risk due to kinetic-chain demands. Effective prevention includes physical conditioning, technique optimization, workload regulation and psychosocial strategies. Future research should prioritize prospective studies evaluating multifactorial prevention programs and functional screening, integrating biomechanics, workload, and psychosocial factors across ages, sexes, along with competition levels.